Do nonresident fathers compensate for a lack of household resources? The associations between paternal involvement and children's cognitive and educational assessments in the UK - Tanskanen AO; Erola J (ELSEVIER SCI LTD, 2022)
This article investigated the associations between nonresident fathers' involvement and cognitive and educational achievements in children. In particular, we tested the resource compensation model, which predicts that the involvement of nonresident fathers should compensate for the lack of household resources and that the effect should be strong, particularly in families with low resources. We use the British Millennium Cohort Study (n = 3445), in which 11-year-old children's cognitive and educational assessments were measured using the British Ability Scale and household resources were measured using maternal education and occupation, family income, and number of books in the home (i.e., cultural capital). We found that the involvement of nonresident fathers was associated with higher scores more strongly in families with the lowest level of cultural capital, compared with others. However, nonresident fathers' involvement was not associated with child scores more strongly in lower resource households than in higher resource households, when the resources were measured by maternal education and occupation and by family income. The results showed that, although the involvement of nonresident fathers might compensate for a lack of household resources, the effect tends to vary between resource types. (C) 2017 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license